Welding engineering an introduction : - Phillips, David H. (Wiley, 2016)
Provides an introduction to all of the important topics in welding engineering. It covers a broad range of subjects and presents each topic in a relatively simple, easy to understand manner, with emphasis on the fundamental engineering principles.